Cardiac rehabilitation after transcatheter versus surgical prosthetic valve implantation for aortic stenosis in the elderly. (29th August 2020) - Russo, Nicola; Compostella, Leonida; Tarantini, Giuseppe; Setzu, Tiziana; Napodano, Massimo; Bottio, Tomaso; D'Onofrio, Augusto; Isabella, Gianbattista; Gerosa, Gino; Iliceto, Sabino; Bellotto, Fabio
Abstract: Background: Transcatheter aortic valve implantation plays a leading role in the management of aortic stenosis in patients with comorbidities but no data are available about cardiac rehabilitation in these subjects. This study aimed to compare safety and efficacy of an early, exercise-based, cardiac rehabilitation programme in octogenarians after a traditional surgical aortic valve replacement versus transcatheter aortic valve implantation. Methods: Seventy-eight consecutive transcatheter aortic valve implantation patients were studied in order to evaluate the effect of an exercise-based cardiac rehabilitation programme in comparison to 80 of a similar age having surgical aortic valve replacement. Functional capacity was assessed by a 6 min walking test on admission and at the end of the programme. When possible, a cardiopulmonary exercise test was also performed before discharge. Results: The two groups were similar in terms of gender and length of stay in cardiac rehabilitation; as expected, the transcatheter aortic valve implantation group had more comorbidities but no major complications occurred in either group during rehabilitation. All patients enhanced autonomy and mobility and were able to walk at least with the assistance of a stick. In those patients who were able to perform the 6 min walking test, the distance walked at discharge did not significantly differ between the groups (272.7 ± 108 vs. 294.2 ± 101 m, p = 0.42), neither did the exercise capacity assessed by cardiopulmonary exercise test (peak-VO2 12.5 ± 3.6 vs. 13.9 ± 2.7 ml/kg/min, p = 0.16). Conclusions: Cardiac rehabilitation is feasible, safe and effective in octogenarian patients after transcatheter aortic valve implantation as well as after traditional surgery. An early cardiac rehabilitation programme enhances independence, mobility and functional capacity and should be highly encouraged.